Bibliometric analysis of the 100 most-cited dental articles on COVID-19 - Nurullah Türker; Özlem Daltaban (Acta Odontologica Turcica, 2023)
Objective: This study aimed to bibliometrically characterize the top 100 most cited (T100) dental articles about COVID-19. Materials and Method: In the present study, the Web of Science core collection database was used to identify the T100 dental articles on COVID-19 in the category of "Dentistry, Oral Surgery and Medicine'' on May 19, 2021. Among the included top most cited articles, the following parameters were recorded and bibliometrically analyzed as article title, publication date, authorship, institution and country of origin, journals, with its impact factor (IF) and quartile, number of citations, study design, study topic, and level of evidence (LOE). Results: The mean citation count of the T100 dental articles on COVID-19 was 32.77 ± 97.31. The T100 dental articles were published in 43 different journals. The number of citations was positively correlated with journal IF (p<0.05; Spearman’s rank test). Four papers were cited more than 100 times. Although 521 authors from 32 different countries contributed to the articles, only 28% had international collaborations. The most productive countries were the USA and China. Of the T100 articles, 50% were of LOE VII and 32% LOE V. The most common study type was narrative reviews (n=38) followed by cross-sectional studies (n=26). Conclusion: This bibliometric analysis of the T100 dental articles on COVID-19 presents the current status, relationships between disciplines, and popular research trends. According to our analysis, the majority of the published articles are of low level of evidence. The establishment of further international cooperation between researchers may improve the scientific quality of future dentistry articles on COVID-19.